"More Than Words": Social Validation in Close Relationships. (November 2014) - Koudenburg, Namkje; Gordijn, Ernestine H.; Postmes, Tom
Conversations are susceptible to many disturbances: A speaker's hesitations, distractions, or, when communicating online, technical hiccups that may cause brief delays. Research among previously unacquainted individuals revealed that brief disruptions in conversational flow can have profound social consequences: Silences or delays in mediated communication threaten the need to belong and validate one's ideas. The present research, however, shows that when occurring in close relationships, flow disruptions may be ironically beneficial. We hypothesized that when flow disruptions occur, partners fall back on their relationship beliefs to infer mutual agreement and the existence of a shared reality. When a relationship is perceived as secure, partners may believe that "no words are needed" to understand each other. Flow disruptions can thus paradoxically make shared cognitions accessible and foster feelings of social validation. Data from two experiments, using partners in different types of relationships, supported this hypothesis.